Sociological Perspectives on Earth System Modeling. (19th December 2019) - Grundmann, Reiner; Rödder, Simone
Abstract: How can we understand climate change from a sociological perspective? In asking this question, we assume that Sociology has something to contribute to such an enterprise. The argument that we put forward is twofold: We argue that Sociology provides a much needed alternative to two dominant approaches that have influenced public discourse, behaviorist theories, mainly employed in Economics, and a belief in the centrality of science in policy making ("evidence first"), mainly entertained by physical scientists. We critically discuss both approaches, showing the limits of behaviorism and the linear model of policy making and provide an alternative framework, which emphasizes the role of social action, of organizations, and of structural differences between different social worlds. We then apply our framework to assess the role of evidence at the climate science‐policy interface and the Intergovernmental Panel on Climate Change (IPCC) as a boundary organization in particular. We argue that science and politics follow different logics and that the IPCC is simultaneously both more political and less policy relevant than its self‐description as "policy‐relevant, never policy prescriptive" tries to make us believe. We conclude that a depoliticization of politics by IPCC expert advice and a politicization of climate science occur simultaneously and mutually reinforce one another. The result is a lack of progress in climate policy as science has taken center stage but is unable to offer political solutions. Key Points: Applying sociological concepts, we assess how climate change has been framed by two influential disciplines (economics and the physical sciences) We provide an alternative framework which emphasizes the role of social action, of organizations, and of structural differences between different social worlds We conclude that science and politics follow different logics and that boundary organizations such as the IPCC cannot escape this harsh reality